Increasing Customer Loyalty through Customer Relationship Management, Product Quality, and Digital Marketing - Surjana, Fulien; Suparmi, Suparmi (Faculty of Economics and Business UNTAG Semarang, 2025)
This study aims to determine the effect of Customer Relationship Management, product quality, and digital marketing on customer loyalty at PT. Tugu Beton Semesta Abadi Semarang. The population used in this study were all companies or organizations that use services from PT. Tugu Beton Semesta Abadi Semarang had 562 companies, while the sample size was 85 respondents. The sampling technique used was purposive sampling. The data source used was primary data, with data collection using a questionnaire. The data analysis technique used was multiple linear regression analysis. The results of the hypothesis test showed that Customer Relationship Management, product quality, and digital marketing had a positive and significant effect on customer loyalty. The coefficient of determination value was 0.655, meaning that Customer Relationship Management, product quality, and digital marketing can explain the variation in customer loyalty variables by 65.5 percent, so it still requires follow-up with further research, especially regarding customer loyalty. The study concludes that CRM, product quality, and digital marketing also have a positive effect on customer loyalty. The suggestions for managers are must increase the technology utilization, improve product innovation development, and enhance digital marketing.